An innovative methodology for seismic retrofitting of existing RC buildings by metal shear panels. - De Matteis, G. (Earthquake engineering & structural dynamics.)
In the present paper, the seismic upgrading of existing reinforced concrete (RC) structures by means of steel and pure aluminium shear panels is examined. After a preliminary experimental evaluation of the performance of the bare RC structure, a design approach based on the capacity spectrum method has been developed according to the procedure provided in the ATC 40 American guidelines. First, the geometrical configuration of the applied shear panels has been defined according to simplified analytical relationships, while appropriate steel members have been designed to allow the insertion of shear panels in the existing RC structure. Then, complex finite element models have been implemented in order to check the reliability of the proposed design procedure. Also, a numerical evaluation of the global response of the upgraded structure has been processed aiming at evaluating the interaction between the RC structure and the metal devices. Finally, the effectiveness of the applied shear panels has been proven by means of full-scale experimental tests, which confirmed the significant improvement of the RC structure performance, in terms of strength, stiffness and deformation capacity.